Empty - Weyn, Suzanne (New York : Scholastic Press, 2010)
When, just ten years in the future, oil supplies run out and global warming leads to devastating storms, senior high school classmates Tom, Niki, Gwen, Hector, and Brock realize that the world as they know it is ending and lead the way to a more environmentally-friendly society.
Young Adult
Young Adult
Keywords: Ecology -- Juvenile fiction; Environmental degradation -- Juvenile fiction; Fossil fuels -- Juvenile fiction; Hurricanes -- Juvenile fiction; Renewable energy sources -- Juvenile fiction; Social change -- Juvenile fiction; Ecology -- Fiction; Environmental degradation -- Fiction; Fossil fuels -- Fiction; Hurricanes -- Fiction; Renewable energy sources -- Fiction; Science fiction; Social change -- Fiction; Ecology -- Fiction; Environmental degradation -- Fiction; Fuel -- Fiction; Hurricanes -- Fiction; Renewable energy sources -- Fiction; Science fiction; Social change -- Fiction; Science fiction